Acoustic monitoring shows invasive beavers Castor canadensis increase patch‐level avian diversity in Tierra del Fuego. Issue 12 (6th October 2021) - Francomano, Dante; Valenzuela, Alejandro E. J.; Gottesman, Benjamin L.; González‐Calderón, Alvaro; Anderson, Christopher B.; Hardiman, Brady S.; Pijanowski, Bryan C.
Abstract: The North American beaver Castor canadensis is an invasive species in the Tierra del Fuego Archipelago. Due to this biological invasion, Argentina and Chile signed an agreement to restore affected ecosystems by eradicating beavers. In southern Patagonia, the beavers' ecological impacts are well studied, but there is a relative lack of information on how their invasion (and potential removal) could affect bird communities. In the southern portion of Tierra del Fuego's 'big island' ( Isla Grande ), we conducted passive acoustic monitoring and avian point counts in intact riparian forests, beaver ponds and beaver meadows (i.e. drained ponds) to assess spatial and seasonal differences in acoustic activity and avian abundance, species diversity and functional diversity. During spring and summer, acoustic activity was significantly higher in meadows than in forests, with ponds exhibiting intermediate values. Abundance and species diversity exhibited similar patterns, driven largely by resident passerines, while functional diversity tended to be highest in ponds, largely due to ducks and raptors. Effects were weaker in fall and winter. Acoustic metrics exhibited moderate to strong correlations with all point‐count‐derived metrics. Synthesis and applications . At the patch level, the avian community was more abundant and diverse in beaver‐modified habitats than in intact riparian forests, though communities in modified patches may not differ substantially from those in analogous natural open and wetland habitats. Dam breaching and pond drainage did not yield a return to an intact forest bird community, indicating that active reforestation may be necessary to restore avian communities to pre‐beaver conditions in the short to medium term, as sought by the binational agreement. Given the immense challenges of eradication and restoration, its social‐ecological costs and benefits—including those related to avifauna—should be thoroughly considered in establishing goals or indicators of success. Abstract : At the patch level, the avian community was more abundant and diverse in beaver‐modified habitats than in intact riparian forests, though communities in modified patches may not differ substantially from those in analogous natural open and wetland habitats. Dam breaching and pond drainage did not yield a return to an intact forest bird community, indicating that active reforestation may be necessary to restore avian communities to pre‐beaver conditions in the short to medium term, as sought by the binational agreement. Given the immense challenges of eradication and restoration, its social‐ecological costs and benefits—including those related to avifauna—should be thoroughly considered in establishing goals or indicators of success. Resumen: El castor norteamericano Castor canadensis es una especie invasora en el Archipiélago de Tierra del Fuego. Debido a esta invasión biológica, Argentina y Chile firmaron un acuerdo para restaurar los ambientes afectados por medio de la erradicación. Los impactos ecológicos del castor en el sur de la Patagonia son bien estudiados, pero existe una relativa falta de información sobre cómo su invasión (y potencial remoción) podría afectar a las comunidades de aves. En la parte sur de la Isla Grande de Tierra del Fuego, llevamos a cabo un monitoreo acústico pasivo y conteos por puntos de aves en bosques ribereños intactos, embalses de castor y praderas de castor (embalses drenados) para evaluar las diferencias espaciales y estacionales de la actividad acústica, la abundancia y diversidad de aves así como su diversidad funcional. Durante la primavera y el verano, la actividad acústica fue significativamente mayor en las praderas que en los bosques, y los embalses mostraron valores intermedios. La abundancia y la diversidad de especies exhibieron patrones similares, impulsados principalmente por paseriformes residentes, aunque la diversidad funcional tendió a ser mayor en los embalses, en gran parte debido a los patos y aves rapaces. Los efectos fueron más débiles en otoño e invierno. Las métricas acústicas mostraron correlaciones de moderadas a fuertes con todas las métricas derivadas de los conteos por puntos. Síntesis y aplicaciones . A nivel de parche, la comunidad de aves fue más abundante y diversa en hábitats modificados por castores que en los bosques ribereños intactos, aunque las comunidades en parches modificados pueden no diferir sustancialmente de aquellas en hábitats naturales análogos abiertos y humedales. La ruptura de diques y el drenado de los embalses no produjeron un retorno a una comunidad de aves semejante a la del bosque intacto, indicando que puede ser necesaria una reforestación activa para restaurar las comunidades de aves a condiciones previas al castor en el corto y mediano plazo, como se busca por el acuerdo binacional. Dados los inmensos desafíos que implican la erradicación y restauración, sus costos y beneficios socio‐ecológicos—incluidos los relacionados con la avifauna—deberían ser considerados a fondo al establecer metas o indicadores de éxito.